Struck by the Potentials of Cannabusiness - Ernesto Abalo (tripleC: Communication, Capitalism & Critique, 2019)
This study examines the reporting on legal cannabis in order to explore the operation of neoliberal ideology in journalistic discourse. Cannabis legalisation is here understood as a way for capitalism to create new market opportunities, besides being a turn away from the so-called ‘war on drugs’. The study understands neoliberalism as operating via market-based logics that are interrelated with other social logics, such as those pertaining to journalism (Phelan 2014). Critical discourse analysis is used for studying Swedish newspaper reporting on legal cannabis between 2013 and 2018. The study shows that a struggle between market-based logics and journalistic practices is visible, where journalism has difficulties in challenging core tenets of neoliberal ideology. The article concludes with a discussion of how the current conditions of journalism limit its ability to challenge neoliberal perspectives.